Vieses de dados ecológicos de bivalves de água doce da América do Sul - Souza, Miriã Ferraz e (2023)
Taxonomic, temporal and geographic information is increasingly accessible, thanks to the advancement of digitization and availability of primary biodiversity data. For some ecosystems and biological groups, such as freshwater invertebrates, the knowledge and availability of these data are still scarce. In this paper, we synthesize knowledge on freshwater bivalves from South America. To do so, we (1) collected the most comprehensive, manually compiled distribution dataset with publicly available data for South American bivalves from 222 years; (2) identified taxonomic and geographic biases over time; and finally (3) explored the dimensions and magnitude of these primary data at the level of freshwater ecoregions. We found that only 25% of the records for native species, are complete, while for invasive species this percentage is much higher, 61%. The families Mycetopodidae and Hyriidae showed the highest number of occurrence records with complete primary data; and they also showed temporal and spatial bias. More than 150 years of native species records, in 1,999 was the year with the highest proportion of occurrence records. We found an imbalance in the taxonomic representation of native species families, in which Sphaeriidae is the most under-represented, while Mycetopodidae and Hyriidae are the most over-represented and have higher proportions of occurrences with more than 20 distinct points in geographic space. Our results are to enhance taxonomic and geographic knowledge for the group, which are potentially important to direct future work, as understanding biodiversity enables better strategies to be devised for those regions that are poorly known.